MACHINABILITY STUDY AND OPTIMIZATION OF TOOL LIFE AND SURFACE ROUGHNESS OF FERRITE – BAINITE DUAL PHASE STEEL - Hegde, Ananda; Hindi, Jamaluddin; B.M, Gurumurthy; Sharma, Sathyashankara; Kini, Achutha (Journal of Applied Engineering Science, 2022)
Aim of this present research work is to obtain the machining parameters to optimize the tool life and surface roughness for ferrite-bainite dual phase steel. Machinability tests are carried out using orthogonal array of 27, the Taguchi method, in which the machining parameters are considered as control factors. The effect of speed, feed and depth of cut on tool life and surface roughness of dual phase structure steel is analysed using ANOVA. Regression analysis is used to obtain the equations for predicting the tool life and surface roughness. Experiment is conducted using uncoated carbide insert tool by varying the process parameters. Optimum tool life and surface is analysed using Response Surface Methodology. Hardness and microstructure revealed the dual phase condition in different intercritical zones. It is found that hardness improves as the intercritical temperature is increased from 750 to 770°C. Experimental results prove that dual phase structure has better machining characteristics at an intercritical temperature of 750°C.